KEPEMILIKAN MANAJERIAL DAN MODAL INTELEKTUAL SEBAGAI PREDIKTOR PERATAAN LABA DAN IMPLIKASINYA TERHADAP NILAI PERUSAHAAN - Gayatri, Ida Ayu; Astika, I.B Putra; Suputra, I D.G. Dharma (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2016)
This study aimed to provide empirical evidence of the influence of managerial ownership and intellectual capital to the firm value directly or indirectly through income smoothing as an intervening variable. The population used in this study is all companies listed on the Stock Exchange period 2009 to 2013 which amounted to 693 companies. By using purposive sampling technique, it is obtained 36 samples. The data analysis technique used is the path analysis. Results of this study prove that income smoothing is not an intervening variable or unable to mediate the relationship between managerial ownership to firm value as well as the relationship between intellectual capital to firm value.
Keywords: Firm Value, Income Smoothing, Managerial Ownership, Intellectual Capital